On Comonotony Approximation in Quasi Normed Space - Abd AL-Sada, Nada Zuhair (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we are introduce the relationship between the best approximation by the polynomial and modules of smoothness , and the modules of smoothness , in quasi normed space ,and the polynomial which change its comonotone approximation with the function at every point in an interval .